Bimetal MOFs three-dimensional biomass composite material as well as preparation method and application thereof
By growing iron-manganese gallate bimetallic MOFs in situ on cotton fibers, activating hydrogen peroxide as a catalyst, the problems of low utilization rate and narrow pH adaptation range in tetracycline degradation are solved, and efficient and environmentally friendly degradation effect is achieved, and it is convenient for Recycle.
Patent Information
- Application Number
- CN202411350625.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art has problems such as low utilization rate, difficulty in sludge treatment and narrow pH adaptation range in the degradation of tetracycline, and the monometallic MOFs catalyst is not efficient and the powder form is inconvenient for recycling.
The hydrothermal synthesis method is used to grow iron-manganese gallate bimetallic MOFs in situ on cotton fibers, act as a catalyst to activate hydrogen peroxide to produce free radicals, attack tetracycline and decompose into CO2 and H2O, and use the synergistic effect of bimetallic MOFs to improve catalytic performance and The pH adaptation range and the MOFs are fixed on the three-dimensional substrate material for easy recycling.
It achieves green, environmentally friendly and fast tetracycline degradation, has high removal rate, strong anti-interference ability, is easy to recover, has good stability, and is suitable for a wide pH range.
Smart Images

Figure CN119237018A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the multi-technical fields of three-dimensional biomass materials, metal organic framework materials, catalytic degradation and organic matter removal, and specifically relates to a bimetallic MOFs three-dimensional biomass composite material and a preparation method and application thereof. Background Art
[0002] The invention and application of antibiotics have made significant contributions to human development. Among them, tetracycline (TC) is widely used in aquaculture and human disease treatment due to its broad spectrum and low price. However, only a small part of the TC used in large quantities can be fully utilized by humans and animals. Most of it is excreted from the body in the form of prototype or metabolites through feces, and finally accumulates in the environment with the application of manure and wastewater discharge, causing serious pollution and posing a serious threat to the ecological environment and human health. Therefore, it is very necessary to quickly degrade and remove TC. At present, the methods for removing TC mainly include membrane filtration, ion exchange, microbial treatment, adsorption and Fenton advanced oxidation degradation. Among them, Fenton advanced oxidation method has the characteristics of strong oxidative degradation ability, no pollution, environmental protection, and simple operation, and is considered to be one of the most promising methods in TC removal technology. However, the traditional Fenton reaction still has some shortcomings, such as low utilization rate of hydrogen peroxide, difficult sludge treatment, and low pH adaptability range. In order to improve these shortcomings, some scholars have explored Fenton-like reactions. The Fenton-like reaction refers to a method of directly using an iron-containing solid catalyst or loading iron ions onto a solid catalyst to catalyze hydrogen peroxide to produce free radicals. However, the efficiency of single metal MOFs as catalysts to catalyze hydrogen peroxide to produce free radicals is not high, and powdered MOFs are not easy to recycle during use. Metal organic framework compounds (MOFs) are crystalline porous materials with regular or pore structures that are constructed by connecting inorganic metal centers and organic functional groups through coordination bonds. MOFs are a promising catalyst in Fenton-like degradation systems. Common MOFs include IRMOF, ZIF, MIL, UIO and other series. However, the organic ligands of these MOFs are some aromatic carboxylic acids and dicarboxylic acids. Most of these organic compounds have certain toxicity. Therefore, it is very necessary to explore some non-toxic and environmentally friendly organic ligands. Summary of the invention
[0003] In view of the above technical problems, the present invention provides a bimetallic MOFs three-dimensional biomass composite material and its preparation method and application. Gallic acid iron manganese bimetallic MOFs are grown in situ on the surface of plasma-treated cotton fibers by hydrothermal synthesis to obtain a three-dimensional biomass composite material Fe / Mn X-MOFs@CF, which is used as a catalyst to activate H2O2 to generate free radicals, and the generated free radicals will attack tetracycline TC and decompose it into small molecules CO2 and H2O. The degradation system of the present invention has the advantages of being green, environmentally friendly, fast degradation rate, high removal rate, strong anti-interference ability, easy recovery, etc., and has been successfully used for the degradation of tetracycline TC.
[0004] Gallic acid in the present invention is a polyphenolic organic compound, which has a carboxylic acid group with the ability to coordinate with metals. In addition, gallic acid is widely present in plants such as palm leaf rhubarb, large leaf eucalyptus, and cornus officinalis, and is a non-toxic organic matter that is friendly to humans and the environment. Therefore, gallic acid MOFs is a very potential catalyst. The slow conversion of metal valence states in monometallic MOFs affects the low efficiency of free radical generation, while bimetallic MOFs, as a solid catalyst for Fenton-like reactions, have high catalytic performance, a wide pH adaptation range, and excellent stability. In addition, the synergistic effect of the two metals in the bimetallic MOFs catalyst can improve the utilization rate of hydrogen peroxide, which is beneficial to improving the catalytic performance. At the same time, in order to ensure that the powdered MOFs are easy to recycle during use, the MOFs are fixed on a three-dimensional substrate material. Based on this, the present invention in situ grows Fe, Mn bimetallic MOFs (Fe / Mn3-MOFs@CF) with gallic acid as an organic ligand on biomass cotton fibers, and the three-dimensional fiber material has the characteristics of high catalytic performance, wide pH adaptation range, green, and environmental protection.
[0005] The present invention achieves the above technical objectives through the following technical means.
[0006] A method for preparing a bimetallic MOFs three-dimensional biomass composite material comprises the following steps:
[0007] Step S1, cotton fiber CF pretreatment:
[0008] The cotton fiber CF was washed alternately with deionized water and ethanol, and washed with ethanol for the last time, and then dried; the dried cotton fiber CF was cleaned with plasma to further remove impurities on the cotton fiber surface and enrich its surface with oxygen functional groups, which is convenient for the in-situ growth of Fe / Mn3-MOFs;
[0009] Step S2: Bimetallic MOFs three-dimensional biomass composite material Fe / Mn X - Preparation of MOFs@CF:
[0010] FeCl2·4H2O and MnCl2·4H2O were dissolved in deoxygenated deionized water to obtain a bimetallic solution, and cotton fiber CF was immersed in the bimetallic solution to make it fully react with metal ions. Gallic acid was dissolved in potassium hydroxide KOH solution to obtain a gallic acid solution. Subsequently, the gallic acid solution was added to the bimetallic solution containing cotton fiber CF and polyvinyl pyrrolidone PVP was added and stirred to mix evenly. The mixed solution was subjected to hydrothermal heating reaction, cooled to room temperature, washed and dried to obtain a bimetallic MOFs three-dimensional biomass composite material Fe / Mn X -MOFs@CF, X represents the doping amount of MnCl2·4H2O.
[0011] Preferably, the CF plasma cleaning time in step (1) is 1 min. If the time is too long, the groups will be destroyed, and if the time is too short, the cleaning will not be thorough.
[0012] In the above scheme, in step S2, FeCl2·4H2O, MnCl2·4H2O and gallic acid are prepared in a molar mass ratio of 10:3:15; the mass ratio of deoxygenated deionized water to polyvinylpyrrolidone PVP is 100:1; and X is 1-10.
[0013] In the above scheme, the Fe / Mn X -MOFs@CF where X is 3, the obtained bimetallic MOFs three-dimensional biomass composite material is Fe / Mn3-MOFs@CF.
[0014] In the above scheme, in step S2, the cotton fiber CF is immersed in the bimetallic solution for 8 hours; the hydrothermal temperature in the hydrothermal heating reaction is 80° C., and the reaction time is 15 hours.
[0015] Preferably, in step S2, the mass of FeCl2·4H2O is 1.98 g (10 mmol), the mass of MnCl2·4H2O is 0.59 g (3 mmol), the volume of deoxygenated deionized water for dissolving FeCl2·4H2O and MnCl2·4H2O is 10 mL, the mass of cotton fiber CF is 0.5 g, the mass of gallic acid is 2.82 g (15 mmol), the KOH solution for dissolving gallic acid is 20 mL with a concentration of 1.25 mol, the mass of PVP added after mixing is 0.3 g, the hydrothermal temperature is 80°C, and the reaction time is 15 h.
[0016] Preferably, the deoxygenated deionized water in step S2 is obtained by passing nitrogen gas through 50 mL of deionized water for 30 minutes.
[0017] Preferably, the washing in step S2 is performed by washing with deionized water three times, and the last washing is performed with ethanol, and the washed product is dried at 60° C. for 6 hours.
[0018] A bimetallic MOFs three-dimensional biomass composite material is prepared according to the preparation method of the bimetallic MOFs three-dimensional biomass composite material.
[0019] An application of a bimetallic MOFs three-dimensional biomass composite material prepared according to the preparation method of the bimetallic MOFs three-dimensional biomass composite material in degrading tetracycline TC.
[0020] In the above scheme, the use of the bimetallic MOFs three-dimensional biomass composite material for catalyzing hydrogen peroxide H2O2 to produce free radicals for oxidative degradation of tetracycline TC comprises the following steps:
[0021] The bimetallic MOFs three-dimensional biomass composite material Fe / Mn3-MOFs@CF was weighed and added to the treated water containing tetracycline TC, and then hydrogen peroxide H2O2 was added to adjust the pH. The bimetallic MOFs three-dimensional biomass composite material Fe / Mn3-MOFs@CF catalyzed H2O2 to produce free radicals to degrade and remove TC.
[0022] Furthermore, the dosage of the bimetallic MOFs three-dimensional biomass composite material Fe / Mn3-MOFs@CF is 0.1 g·L -1 ~0.5g·L -1 The amount of hydrogen peroxide H2O2 used is 5mM to 50mM, and the pH is adjusted to 2 to 11.
[0023] Furthermore, the dosage of the bimetallic MOFs three-dimensional biomass composite material Fe / Mn3-MOFs@CF is 0.4 g·L -1 .
[0024] Furthermore, the usage amount of hydrogen peroxide H2O2 is 30mM.
[0025] Preferably, the preparation of tetracycline TC solution comprises the following specific steps:
[0026] (1) Preparation of TC mother solution
[0027] Weigh 100 mg TC into a beaker and dissolve it by ultrasonication. Then, dilute it to 200 g·L using a 500 mL volumetric flask. -1 The TC mother solution was kept for future use and stored in a 4°C refrigerator away from light.
[0028] (2) Drawing of the TC solution standard curve
[0029] The mother solution was diluted to different concentration gradients (1 g·L -1 , 5g·L -1 , 10g·L -1 、30g·L-1 , 50g·L -1 ) Then, an ultraviolet spectrophotometer was used to detect the absorbance of TC at different concentrations at 358 nm, and a standard curve was drawn based on the linear relationship between the absorbance of TC at different concentrations at 358 nm and its concentration value for subsequent calculation of TC concentration.
[0030] Preferably, the bimetallic MOFs three-dimensional biomass composite material Fe / Mn3-MOFs@CF is used to catalyze hydrogen peroxide H2O2 to produce free radicals for oxidative degradation of TC, comprising the following steps:
[0031] (1) Under certain conditions, add 20 mL of 50 g·L -1 TC solution, then weigh 0.008g Fe / Mn3-MOFs@CF material and add it, and finally add 65μL H2O2 (30%), and then place the glass bottle in a constant temperature shaker with a rotation speed of 200rpm.
[0032] (2) Samples are taken at regular intervals to test the TC concentration, and the TC degradation and removal efficiency is calculated based on the current concentration and the initial concentration.
[0033] Preferably, the certain conditions in step (1) are a temperature of 25° C. and a pH of 6.
[0034] Preferably, the time intervals in step (2) are 0 min, 5 min, 10 min, 20 min, 30 min, 40 min, and 50 min respectively.
[0035] Preferably, the sampling in step (2) is performed by using a 1 mL syringe and filtering through a 0.22 μm filter membrane.
[0036] Preferably, the TC degradation removal efficiency in step (2) is calculated based on the TC concentration at the time of sampling and the initial TC concentration.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The present invention prepares a bimetallic MOFs three-dimensional biomass composite material Fe / Mn by an in-situ synthesis method. X -MOFs@CF, the catalytic performance of the obtained composite material is improved compared with that of the single metal Fe-MOFs@CF, and the Fenton system has good anti-interference ability and a wider pH adaptability range.
[0039] (2) The present invention combines bimetallic MOFs with biomass cotton fibers, which, on the one hand, improves the catalytic performance; on the other hand, the three-dimensional cotton structure as a substrate enables powdered MOFs to be easily recycled during use, greatly improving the practical usability of MOFs.
[0040] (3) In the present invention, green, environmentally friendly and non-toxic biomass gallic acid is used as an organic ligand to replace the traditional dicarboxylic acid compound organic ligand, thereby greatly reducing environmental risks.
[0041] (4) The Fe / Mn3-MOFs@CF prepared by the present invention catalyzes H2O2 for TC degradation and removal, with good stability and high removal efficiency, and a removal rate of 89.55% can be achieved after 50 minutes of degradation.
[0042] (5) The Fenton oxidation degradation system constructed by the present invention is green and environmentally friendly, has good degradation and removal effects, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a diagram showing the mechanism of the present invention for TC degradation and removal.
[0044] Figure 2 Fe-MOFs@CF and Fe / Mn X -Comparison of the efficiency of TC degradation by H2O2 catalyzed by MOFs@CF, among which, Figure 2 (a) Fe-MOFs@CF and Fe / Mn X -MOFs@CF degradation efficiency line graph, Figure 2 (b) is a comparison chart of degradation rate constants.
[0045] Figure 3 is a scanning electron microscope image of a material according to an embodiment of the present invention, wherein Figure 3 (a) is a scanning electron microscope image of pure cotton fiber. Figure 3 (b) is a high-magnification scanning electron microscope image of pure cotton fiber. Figure 3 (c) is the overall scanning electron microscopy image of Fe-MOFs@CF. Figure 3 (d) is a local magnified scanning electron microscopy image of Fe-MOFs@CF. Figure 3 (e) is the overall scanning electron microscopy image of Fe / Mn3-MOFs@CF. Figure 3 (f) is a local magnified scanning electron microscope image of Fe / Mn3-MOFs@CF.
[0046] Figure 4 This is an element distribution diagram of Fe / Mn3-MOFs@CF according to one embodiment of the present invention, wherein Figure 4 (a) is the overall scanning electron microscopy image of Fe / Mn3-MOFs@CF. Figure 4(b) is the distribution diagram of N element in Fe / Mn3-MOFs@CF. Figure 4 (c) is the C element distribution diagram in Fe / Mn3-MOFs@CF. Figure 4 (d) is the distribution diagram of Fe element in Fe / Mn3-MOFs@CF. Figure 4 (e) is the distribution diagram of O element in Fe / Mn3-MOFs@CF. Figure 4 (f) is the distribution diagram of Mn element in Fe / Mn3-MOFs@CF.
[0047] Figure 5 The effect of Fe / Mn3-MOFs@CF and H2O2 system on TC degradation under different dosage conditions according to one embodiment of the present invention is shown in FIG. Figure 5 (a) The effect of Fe / Mn3-MOFs@CF usage on TC degradation efficiency. Figure 5 (b) Effect of H2O2 usage on TC degradation efficiency.
[0048] Figure 6 is the effect of pH on TC degradation efficiency, where Figure 6 (a) is the degradation efficiency diagram of TC under different pH conditions. Figure 6 (b) is the rate constant of TC degradation under different pH conditions.
[0049] Figure 7 is the effect of different interferents on the degradation of TC in this system, where Figure 7 (a) is the effect of various inorganic anions on the system, Figure 7 (b) The effect of various concentrations of organic humic acid on the system. DETAILED DESCRIPTION
[0050] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0051] Example 1
[0052] A method for preparing a bimetallic MOFs three-dimensional biomass composite material comprises the following steps:
[0053] Three-dimensional composite materials Fe-MOFs@CF and Fe / Mn X - Preparation steps of MOFs@CF:
[0054] (1) Cotton fiber CF pretreatment:
[0055] The cotton fiber was pretreated to increase the loading rate of MOFs. Specifically, the cotton fiber CF was washed alternately with deionized water and ethanol three times to remove stains on the surface of fresh cotton. The last time it was washed with ethanol and then dried. The dried cotton fiber CF was plasma cleaned for 1 minute to further remove surface impurities and enrich the surface with oxygen-containing functional groups, which facilitated the in-situ growth of MOFs. Figure 3 (a) is a scanning electron microscope image of pure cotton fiber. Figure 3 (b) is a high-magnification scanning electron micrograph of pure cotton fiber.
[0056] (2) Preparation of three-dimensional composite material Fe-MOFs@CF:
[0057] Through a one-step synthesis method, MOFs are natively grown on the surface of cotton fibers. FeCl2·4H2O is dissolved in deoxygenated deionized water and CF is immersed in it to make it fully react with metal ions. Gallic acid is dissolved in potassium hydroxide (KOH) solution. Then, the gallic acid solution is added to the FeCl2·4H2O solution containing CF and polyvinyl pyrrolidone (PVP) is added and stirred to mix evenly. The mixed solution is hydrothermally heated to a certain temperature, reacted for a period of time, cooled to room temperature, washed and dried.
[0058] The specific preparation of Fe-MOFs@CF is to dissolve 1.98g of FeCl2·4H2O (10mmol) in 10mL of deoxygenated deionized water and immerse 0.5g of CF therein to allow the functional groups on the surface of the cotton fiber to fully react with the metal ions for 8 hours, dissolve 2.82g of gallic acid (15mmol) in 20mL of 1.25mol potassium hydroxide (KOH) solution, then add the gallic acid solution to the FeCl2·4H2O solution containing CF and add 0.3g of polyvinyl pyrrolidone PVP and stir to mix evenly, heat the mixed solution to 80°C by hydrothermal heating, react for 15h, wait until it cools to room temperature, wash with deionized water 3 times and then with anhydrous ethanol, and finally dry at 60°C. Finally, a black three-dimensional fibrous product is obtained. Scanning electron microscope image, such as Figure 3 (c) and Figure 3 As shown in (d), the Fe-MOFs particles are evenly distributed on the surface of cotton fibers, indicating that Fe-MOFs@CF was successfully prepared.
[0059] (3)Fe / Mn X - Preparation of MOFs@CF:
[0060] Fe / Mn X-MOFs@CF was prepared by dissolving 1.98g of FeCl2·4H2O (10mmol) and a certain amount of MnCl2·4H2O in a certain proportion in 10mL of deoxygenated deionized water and immersing 0.5g of CF in it to allow it to fully react with metal ions for 8h, 2.82g of gallic acid (15mmol) was dissolved in 20mL of 1.25mol potassium hydroxide (KOH) solution, and then the gallic acid solution was added to the FeCl2·4H2O and MnCl2·4H2O solutions containing CF, and 0.3g of PVP was added and stirred to mix evenly, and the mixed solution was hydrothermally heated to 80°C, reacted for 15h, cooled to room temperature, washed with deionized water 3 times and then washed once with anhydrous ethanol, and finally dried at 60°C. Finally, a black-purple three-dimensional fibrous product was obtained. Among them, the scanning electron microscope image of Fe / Mn3-MOFs@CF, Figure 3 (e) and Figure 3 (f) is shown. Its element distribution is as follows Figure 4 (a)~ Figure 4 As shown in (f), C, N, O, Fe, and Mn can be detected in the Fe / Mn3-MOFs@CF composite material, indicating that the gallic acid Fe and Mn bimetallic MOFs cotton fiber composite material was successfully prepared.
[0061] Specifically, the amounts of MnCl2·4H2O used in step (3) are 0.197 g (1 mmol), 0.591 g (3 mmol), 0.985 g (5 mmol), 1.379 g (7 mmol), and 1.97 g (10 mmol), respectively.
[0062] Specifically, the Fe / Mn X -MOFs@CF, X represents the doping amount of MnCl2·4H2O, which is 1, 3, 5, 7, and 10, namely, Fe / Mn1-MOFs@CF, Fe / Mn3-MOFs@CF, Fe / Mn5-MOFs@CF, Fe / Mn7-MOFs@CF, Fe / Mn 10 -MOFs@CF.
[0063] Example 2
[0064] The three-dimensional biomass composite material of Fe / Mn3-MOFs@CF prepared by the present invention catalyzes hydrogen peroxide H2O2 to produce free radicals for degrading TC, and the specific steps include:
[0065] (1) Preparation of TC mother liquor
[0066] Weigh 100 mg TC into a beaker and add it to the beaker and sonicate until dissolved. Then, dilute to volume with a 500 mL volumetric flask to prepare 200 mg·L -1The TC stock solution was stored in a 4°C refrigerator for future use.
[0067] (2) Drawing of the TC solution standard curve
[0068] 200mg·L -1 The mother solution was diluted to different concentration gradients (1 mg·L -1 , 5mg·L -1 、10mg·L -1 、30mg·L -1 , 50mg·L -1 ) Then, an ultraviolet spectrophotometer was used to detect the absorbance of TC at different concentrations at 358 nm, and a standard curve was drawn based on the linear relationship between the absorbance of TC at different concentrations at 358 nm and its concentration value for subsequent calculation of TC concentration.
[0069] (3)Fe / Mn X -MOFs@CF catalyzes TC degradation by H2O2
[0070] Add 20 mL of 50 mg·L -1 TC solution, then weigh 0.008gFe / Mn X -MOFs@CF material was added, and finally 65μL of H2O2 (30%) was added, and then the glass bottle was placed in a constant temperature shaker at 200rpm. Fe / Mn3-MOFs@CF catalyzed H2O2 to produce free radicals to degrade and remove TC. 1mL of sample solution was drawn with a syringe at intervals of 0min, 5min, 10min, 20min, 30min, 40min, and 50min, and its absorbance was measured by ultraviolet and brought into the standard curve to calculate the sample TC concentration. According to the ratio of the current concentration to the initial concentration (C t / C0) to evaluate the degradation efficiency.
[0071] Combine Fe-MOFs@CF with Fe / Mn X -MOFs@CF was used to catalyze the degradation of H2O2 to remove TC, and the comparison included the following steps:
[0072] (1) Add 20 mL of 50 mg / L -1 TC solution, and then weighed 0.004g of Fe-MOFs@CF, Fe / Mn1-MOFs@CF, Fe / Mn3-MOFs@CF, Fe / Mn5-MOFs@CF, Fe / Mn7-MOFs@CF, Fe / Mn 10-MOFs@CF material was added, and finally 21.6μL of H2O2 (30%) was added, and then the glass bottle was placed in a constant temperature shaker at 200rpm. The composite material catalyzed H2O2 to produce free radicals to degrade and remove TC. 1mL of sample solution was drawn with a syringe through a 0.22μm filter membrane at intervals of 0min, 10min, 20min, 25min, 30min, 40min, and 50min.
[0073] (2) Calculation of sample concentrations at each time period:
[0074] The absorbance of the TC solution samples extracted at each time period is measured by a UV spectrometer at 358 nm, and then the absorbance at 358 nm is substituted into the calibration curve to calculate the residual TC concentration at each time.
[0075] (3) TC degradation efficiency at each time period is expressed as C t / C0 indicates that the removal rate is calculated as follows:
[0076] r=(1-C t / C0)×100%
[0077] (4) First-order degradation reaction rate fitting equation:
[0078] ln(C t / C0)=kt
[0079] r: TC removal rate; C0: initial TC concentration; C t : is the TC concentration at time t; k is the reaction rate constant;
[0080] (4) Fe-MOFs@CF and Fe / Mn X -Comparison of TC degradation performance of MOFs@CF catalyzed by H2O2:
[0081] Under the condition of ensuring the same conditions such as catalyst dosage, H2O2 dosage, TC concentration, etc., the catalytic performance of single metal composite materials and composite materials with different Fe and Mn ratios were compared. Weigh 0.004g of Fe-MOFs@CF, Fe / Mn1-MOFs@CF, Fe / Mn3-MOFs@CF, Fe / Mn5-MOFs@CF, Fe / Mn7-MOFs@CF and Fe / Mn 10 -MOFs@CF was added in 20 mL and the concentration was 50 g·L -1The glass bottle was then placed in a constant temperature shaker at 200 rpm for the first 20 minutes for adsorption removal. Samples were taken every 10 minutes to test the TC concentration. Finally, 21.6 μL of H2O2 (30%) was added at 20 minutes. 1 mL of sample solution was drawn with a syringe at 25 minutes, 30 minutes, 40 minutes, and 50 minutes to pass through a 0.22 μm filter membrane to test the sample concentration. The experimental results are shown in the figure. Figure 2 As shown in (a), within the first 20 minutes, Fe-MOFs@CF, Fe / Mn1-MOFs@CF, Fe / Mn3-MOFs@CF, Fe / Mn5-MOFs@CF, Fe / Mn7-MOFs@CF and Fe / Mn 10 -MOFs@CF has TC adsorption removal rates of 5.90%, 5.92%, 6.78%, 6.05%, 7.02% and 5.83% respectively. After 20 minutes, H2O2 was added to realize the TC degradation process. At 50 minutes, the TC degradation removal rates were 50.96%, 72.93%, 76.73%, 62.99%, 60.39% and 52.73% respectively. Finally, the first-order degradation reaction rate equation was used for fitting. The results are shown in the figure. Figure 2 As shown in (b), the degradation reaction rate constants are 0.014min -1 、0.027min -1 、0.031min -1 、0.021min -1 、0.019min -1 、0.015min -1 Under the same conditions, Fe / Mn3-MOFs@CF has the best effect on the degradation and removal of TC, so Fe / Mn3-MOFs@CF composite materials were used for characterization and condition screening.
[0082] Example 3
[0083] The effects of different usage amounts of Fe / Mn3-MOFs@CF and H2O2 systems on TC degradation efficiency during the degradation process were compared. The specific steps are as follows:
[0084] (1) Effect of Fe / Mn3-MOFs@CF dosage on TC degradation:
[0085] Under the condition of ensuring the same conditions such as H2O2 dosage, TC concentration, pH value (pH = 6), the dosage of Fe / Mn3-MOFs@CF was changed. 20 mL of 50 mg·L -1TC solution, then weighed 0.002g, 0.004g, 0.006g, 0.008g, and 0.01g Fe / Mn3-MOFs@CF materials and added them, and finally added 21.6μL of H2O2 (30%). After 21.6μL of H2O2 was added to 20mL of TC solution, the H2O2 concentration in the solution was 10mM. The glass bottle was then placed in a constant temperature shaker at 200rpm. The composite material catalyzes H2O2 to produce free radicals to degrade and remove TC. At intervals of 0min, 5min, 10min, 20min, 30min, 40min, and 50min, 1mL of sample solution was drawn with a syringe through a 0.22μm filter membrane, and the TC concentration was measured. The effect of different Fe / Mn3-MOFs@CF usage on the degradation of TC is shown in the figure. Figure 5 As shown in (a), as the dosage of Fe / Mn3-MOFs@CF increases from 0.1 g·L -1 Increase by 0.5 g·L -1 , TC degradation efficiency also gradually increased. After 50 min of degradation, 0.1 g·L -1 , 0.2g·L -1 , 0.3g·L -1 , 0.4g·L -1 , 0.5g·L -1 The removal rates of TC by Fe / Mn3-MOFs@CF were 47.09%, 83.08%, 88.55%, 89.38% and 89.65% respectively. The dosage of Fe / Mn3-MOFs@CF was 0.4 g·L -1 , 0.5g·L -1 When the TC degradation efficiency curves were almost the same and the final removal rates were also very similar, so 0.4 g·L was selected from the cost point of view. -1 The best dosage.
[0086] (2) Effect of H2O2 usage on TC degradation:
[0087] Under the condition of ensuring the same conditions such as Fe / Mn3-MOFs@CF dosage, TC concentration, pH=6, etc., change the H2O2 dosage. Add 20mL of 50mg·L -1TC solution, then weigh 0.008g Fe / Mn3-MOFs@CF material and add it, and finally add 10.8μL, 21.6μL, 43.3μL, 65.0μL, 86.7μL, 108.4μL of H2O2 (30%), 10.8μL, 21.6μL, 43.3μL, 65.0μL, 86.7μL, 108.4μL of H2O2 to 20mL of TC solution, the concentration of H2O2 in the solution is 5mM, 10mM, 20mM, 30mM, 40mM, 50mM respectively. Then place the glass bottle in a constant temperature shaker at a speed of 200rpm. The composite material catalyzes H2O2 to produce free radicals to degrade and remove TC. At intervals of 0 min, 5 min, 10 min, 20 min, 30 min, 40 min, and 50 min, 1 mL of sample solution was drawn by syringe through a 0.22 μm filter membrane, and the TC concentration was measured. Figure 5 As shown in (b), as the H2O2 dosage increases from 5mM to 20mM, the TC degradation efficiency also increases. However, after the H2O2 dosage increases to 30mM, the TC degradation curves almost overlap and the degradation efficiency reaches a plateau. When the H2O2 dosage is 5mM, 10mM, 20mM, 30mM, 40mM, and 50mM, the TC removal rates after 50min of degradation are 87.13%, 88.31%, 89.45%, 89.55%, 88.89%, and 89.42%, respectively. From the perspective of economic cost, 30mM is the best dosage.
[0088] Example 4
[0089] Comparison of the effects of different pH on the degradation of TC by Fe / Mn3-MOFs@CF and H2O2 systems, including the following steps:
[0090] (1) Adjusting TC solutions at different pH values
[0091] 50mg·L -1 The TC solution was divided into 10 portions, each with 60 mL, and then the TC solutions with different pH were adjusted by 0.1 M HCl solution and 0.1 M NaOH solution. The pH values were 2, 3, 4, 5, 6, 7, 8, 9, 10, and 11, respectively. When adjusting the pH, the effect of HCl solution and NaOH solution on the TC concentration was negligible.
[0092] (2) Operation steps of Fe / Mn3-MOFs@CF and H2O2 system for TC degradation under different pH conditions:
[0093] Weigh 0.008 g of Fe / Mn3-MOFs@CF material and add it to different pH volumes (20 mL) and concentrations (50 mg·L)-1 65.0μL of H2O2 (30%) was added to the TC solution, and the concentration of H2O2 was 30mM. The glass bottle was then placed in a constant temperature shaker at a speed of 200rpm. 1mL of sample solution was drawn with a syringe through a 0.22μm filter membrane at intervals of 0min, 5min, 10min, 20min, 30min, 40min, and 50min to test the sample concentration. The TC degradation efficiency curve under different pH conditions is shown in Figure 1. Figure 6 As shown in (a), the degradation efficiency of TC is significantly affected under extremely acidic and alkaline conditions, that is, when the pH is 2, the TC removal rate is 78.27% after 50 minutes of degradation, and when the pH is 10 and 11, the TC removal rates are 71.76% and 59.38% after 50 minutes of degradation, respectively. When the pH is in the range of 3 to 9, the system can maintain a good TC degradation and removal effect, and the removal rates are 86.80%, 86.60%, 86.97%, 88.38%, 85.72%, 81.18%, and 81.17% after 50 minutes of degradation, respectively. Subsequently, the reaction rate constant k under each pH condition was obtained by fitting the first-order degradation reaction rate formula, as shown in the figure: Figure 6 As shown in (b), the reaction rate constants are 0.028 min from pH 2 to 11. -1 、0.032min -1 、0.035min -1 、0.034min -1 、0.036min -1 、0.033min -1 、0.032min -1 、0.031min -1 、0.023min -1 、0.016min -1 The degradation rate constant was the highest at pH 6.
[0094] Example 5
[0095] Comparison of the effects of various interfering substances on the degradation system includes the following steps:
[0096] (1) Operation steps of the effect of inorganic anions on the system:
[0097] Prepare TC solutions containing 5 mM of various anions by dissolving 8.4 mg NaHCO3, 14 mg Na2SO4, 6 mg NaCl, 8.4 mg NaNO3, and 12 mg NaH2PO4 in 20 mL to a concentration of 50 mg / L -1TC solution. Then weigh 0.008g Fe / Mn3-MOFs@CF material and add it to TC solution containing different anions. Finally, add 65.0μL H2O2 (30%), and then place the glass bottle in a constant temperature shaker at a speed of 200rpm. At intervals of 0min, 5min, 10min, 20min, 30min, 40min, and 50min, 1mL of sample solution was extracted with a syringe and passed through a 0.22μm filter membrane. Its concentration was calculated by measuring its absorbance by ultraviolet light, and the relationship between the degradation amount and time was calculated. The results are as follows Figure 7 As shown in (a), H2PO4 is added to the TC solution. - and HCO3 2- , the removal rates of TC after degradation for 50 min were 77.98% and 66.55%, respectively, which were significantly lower than those of the control group (89.57%). - 、NO3 - 、SO4 2- After 50 min of degradation, the removal rates of TC were 88.21%, 87.69%, and 85.98%, respectively. - 、NO3 - 、SO4 2- It has little impact on TC removal rate and has good resistance to anion interference.
[0098] (1) Operation steps of the effect of organic humic acid on the system:
[0099] Formulated to contain 5mg·L -1 、10mg·L -1 , 20mg·L -1 、30mg·L -1 TC solution of humic acid, i.e. 400mL of 50mg·L -1 The TC solution was divided into 4 portions, each with 100 mL. Then 0.5 mg, 1 mg, 2 mg, and 3 mg were weighed and added to 100 mL of TC solution, and dissolved by ultrasound. Then 0.008 g of Fe / Mn3-MOFs@CF material was weighed and added to TC solutions containing different concentrations of humic acid. The volume of the TC solution was 20 mL and the concentration was 50 mg·L -1 Finally, add 65.0μL of H2O2 (30%), and then place the glass bottle in a constant temperature shaker at 200rpm. At intervals of 0min, 5min, 10min, 20min, 30min, 40min, and 50min, use a syringe to extract 1mL of sample solution and pass it through a 0.22μm filter membrane. Calculate its concentration by measuring its absorbance through ultraviolet light, and calculate the relationship between degradation amount and time. The results are as follows Figure 7As shown in (b), as the humic acid concentration increases, the TC degradation efficiency decreases. -1 、10mg·L -1 , 20mg·L -1 、30mg·L -1 Under the same conditions, the TC removal rates after 50 min degradation were 84.00%, 82.70%, 75.82% and 70.91% respectively. The concentration of humic acid in natural waters is generally less than 10 mg·L -1 , so the system has good anti-interference ability of organic matter.
[0100] The Fe / Mn3-MOFs@CF prepared by the present invention not only has a fast degradation rate and high removal efficiency for TC degradation by H2O2, but also has a wide pH adaptability range, breaking the barrier that traditional Fenton-like reactions can only achieve the best effect under acidic conditions. In addition, the system still has a good TC removal ability under the conditions of various anion interferences and organic matter interferences. Compared with traditional powdered catalytic materials, the three-dimensional structure is easy to recycle after use, which greatly improves the actual performance of the material.
[0101] The three-dimensional composite material prepared by the present invention has better pH adaptability and lower toxicity than existing materials in the field of Fenton-like degradation, and can simply and effectively achieve the degradation and removal of TC. In addition, the ideas provided by the present invention can be used to develop degradation for other organic targets, and have good application prospects.
[0102] The present invention uses a hydrothermal synthesis method to grow gallic acid iron manganese bimetallic MOFs in situ on the surface of plasma-treated cotton fiber CF to obtain Fe / Mn3-MOFs@CF, which is used as a catalyst to activate H2O2 to generate free radicals. The generated free radicals will attack TC and decompose it into small molecules CO2 and H2O. In this degradation system, 88.21% of TC degradation removal rate can be achieved within 50 minutes, and at the same time, it still has a good TC removal effect under the condition of pH 2-11. The degradation system has the advantages of fast degradation rate, high removal rate, strong anti-interference ability, easy recovery, etc., and is successfully used for TC degradation.
[0103] It should be understood that although this specification is described according to various embodiments, not every embodiment contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.
[0104] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a bimetallic MOFs three-dimensional biomass composite material, characterized in that: The following steps are involved: Step S1, cotton fiber CF pretreatment: The cotton fiber CF was washed alternately with deionized water and ethanol, and washed with ethanol for the last time, and then dried; the dried cotton fiber CF was cleaned with plasma to further remove impurities on the cotton fiber surface and enrich its surface with oxygen functional groups, which is convenient for the in-situ growth of Fe / Mn3-MOFs; Step S2: Bimetallic MOFs three-dimensional biomass composite material Fe / Mn X - Preparation of MOFs@CF: FeCl2·4H2O and MnCl2·4H2O were dissolved in deoxygenated deionized water to obtain a bimetallic solution, and cotton fiber CF was immersed in the bimetallic solution to make it fully react with metal ions. Gallic acid was dissolved in potassium hydroxide KOH solution to obtain a gallic acid solution. Subsequently, the gallic acid solution was added to the bimetallic solution containing cotton fiber CF and polyvinyl pyrrolidone PVP was added and stirred to mix evenly. The mixed solution was subjected to hydrothermal heating reaction, cooled to room temperature, washed and dried to obtain a bimetallic MOFs three-dimensional biomass composite material Fe / Mn X -MOFs@CF, X represents the doping amount of MnCl2·4H2O.
2. The method for preparing a bimetallic MOFs three-dimensional biomass composite material according to claim 1, characterized in that: In the step S2, FeCl2·4H2O, MnCl2·4H2O and gallic acid are prepared in a molar mass ratio of 10:3:15; the mass ratio of deoxygenated deionized water to polyvinylpyrrolidone (PVP) is 100:1; and X is 1-10.
3. The method for preparing a three-dimensional biomass composite material according to claim 2, characterized in that: The step S2Fe / Mn X -MOFs@CF where X is 3, the obtained bimetallic MOFs three-dimensional biomass composite material is Fe / Mn3-MOFs@CF.
4. The method for preparing a bimetallic MOFs three-dimensional biomass composite material according to claim 1, characterized in that: In the step S2, the cotton fiber CF is immersed in the bimetallic solution for 8 hours; the hydrothermal temperature in the hydrothermal heating reaction is 80° C., and the reaction time is 15 hours.
5. A bimetallic MOFs three-dimensional biomass composite material, characterized in that: It is prepared according to the method for preparing a bimetallic MOFs three-dimensional biomass composite material according to any one of claims 1 to 4.
6. Use of a bimetallic MOFs three-dimensional biomass composite material prepared according to the method for preparing a bimetallic MOFs three-dimensional biomass composite material according to any one of claims 1 to 4 in degrading tetracycline TC.
7. The use of the bimetallic MOFs three-dimensional biomass composite material in degradation of tetracycline TC in water according to claim 6, characterized in that: The use of the bimetallic MOFs three-dimensional biomass composite material according to claim 5 for catalyzing hydrogen peroxide H2O2 to produce free radicals for oxidative degradation of tetracycline TC, The following steps are involved: The bimetallic MOFs three-dimensional biomass composite material Fe / Mn3-MOFs@CF was weighed and added to the treated water containing tetracycline TC, and then hydrogen peroxide H2O2 was added to adjust the pH. The bimetallic MOFs three-dimensional biomass composite material Fe / Mn3-MOFs@CF catalyzed H2O2 to produce free radicals to degrade and remove TC.
8. The use of the bimetallic MOFs three-dimensional biomass composite material according to claim 7 in the degradation of tetracycline TC in water, characterized in that: The dosage of the bimetallic MOFs three-dimensional biomass composite material Fe / Mn3-MOFs@CF is 0.1 g·L -1 ~0.5g·L -1 ; The amount of hydrogen peroxide H2O2 used is 5mM to 50mM, and the pH is adjusted to 2 to 11.
9. The use of the bimetallic MOFs three-dimensional biomass composite material according to claim 8 in degrading tetracycline TC in water, characterized in that: The dosage of the bimetallic MOFs three-dimensional biomass composite material Fe / Mn3-MOFs@CF is 0.4 g·L -1 .
10. The use of the bimetallic MOFs three-dimensional biomass composite material according to claim 8 in degrading tetracycline TC in water, characterized in that: The amount of hydrogen peroxide H2O2 used is 30 mM.
Citation Information
Patent Citations
Preparation method of Fe-MOF loaded activated carbon fiber material
CN111254707A
Method for removing PPCPs in water by catalyzing H2O2 with MIL-100 (Fe / Mn) derivative
CN112225307A
Treatmemt agent for fenton oxidation reaction and advanced oxidation method using the same
KR1020180034838A
Cited By
Nano MOFs loaded bio-based fiber photo-Fenton catalytic material as well as preparation method and application thereof
CN120790237A